Phoomyia, a new genus of Dolichopodinae from the Oriental Region (Diptera: Dolichopodidae) - Naglis, Stefan; Grootaert, Patrick; Brooks, Scott E. (Zootaxa, 2013)
Phoomyia Naglis & Grootaert gen. nov. is described to include two new species of beach-dwelling dolichopodine flies from coastal Sri Lanka and Thailand: Phoomyia srilankensis Naglis & Brooks sp. nov. and Phoomyia thailandensis Naglis & Grootaert sp. nov. The new genus is closely related to the genera Argyrochlamys Lamb and Pseudargyrochlamys Grich-anov, and is distinguished based on characters of the hind leg, and features of the male and female terminalia. Adults of Phoomyia are found on sandy coastal beaches often near the burrows of ghost crabs.